Thermal analysis of a polymorphic azo dye derived from 2-amino-5-nitrothiazole - Campos, Ana M. F. Oliveira (2007)
An azo dye, derived from 2-amino-5-nitrothiazole and a substituted N,N-dimethyl aniline, was studied by various techniques. Two sets of proton signals were obtained by NMR in CDCl3 solution, suggesting that two polymorphs coexist, however only one set of signals is observed in DMSO solution. Differential scanning calorimetry and thermogravimetric analysis were used to confirm the existence of two forms. The events registered during thermal treatment of a sample were assigned to a glass transition, recrystallization and fusion of crystalline compounds. Hot-stage microscopy was used to obtain images of the dye samples at various stages of the heating program and these observations support the interpretation of the calorimetric results.